2005
DOI: 10.1136/thx.2005.040873
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic pulmonary angiography and prognostic significance in patients with acute pulmonary embolism

Abstract: Background: Patients with acute pulmonary embolism (APE) present with a broad spectrum of prognoses. Computed tomographic pulmonary angiography (CTPA) has progressively been established as a first line test in the APE diagnostic algorithm, but estimation of short term prognosis by this method remains to be explored. Methods: Eighty two patients admitted with APE were divided into three groups according to their clinical presentation: pulmonary infarction (n = 21), prominent dyspnoea (n = 29), and circulatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
113
8
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 29 publications
9
113
8
7
Order By: Relevance
“…Although there is some evidence that reconstructed four-chamber views may be superior to axial views for the identification of high-risk patients, 19 several studies have found robust prognostic value using standard axial acquisitions to calculate the RV/LV ratio. 11,12,20 In a large retrospective series of 431 patients, 30-day mortality was 15.6% in patients with RV enlargement (reconstructed four-chamber views), defined as RV/LV ratio >0.9 on MDCT, compared to 7.7% in those without this finding. 6 In the above-mentioned meta-analysis of two studies (with two different RV/LV ratio thresholds, 1.5 and 1.0) including 191 normotensive patients with PE, a 58% (95% CI, 51---65%) overall negative and a 57% positive (95% CI, 49---64%) value of RV dilatation were reported on MDCT for predicting early death, yielding a relative risk for in-hospital mortality of 2.28 (95% CI, 0.9---5.9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is some evidence that reconstructed four-chamber views may be superior to axial views for the identification of high-risk patients, 19 several studies have found robust prognostic value using standard axial acquisitions to calculate the RV/LV ratio. 11,12,20 In a large retrospective series of 431 patients, 30-day mortality was 15.6% in patients with RV enlargement (reconstructed four-chamber views), defined as RV/LV ratio >0.9 on MDCT, compared to 7.7% in those without this finding. 6 In the above-mentioned meta-analysis of two studies (with two different RV/LV ratio thresholds, 1.5 and 1.0) including 191 normotensive patients with PE, a 58% (95% CI, 51---65%) overall negative and a 57% positive (95% CI, 49---64%) value of RV dilatation were reported on MDCT for predicting early death, yielding a relative risk for in-hospital mortality of 2.28 (95% CI, 0.9---5.9).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most studies only include patients with less severe forms of PE, a fact that is highlighted by the low arterial obstruction and RV/LV indices reported. 5,11,12 Two studies focused only on MDCT findings in massive PE, using different definitions. Ocak et al studied three patients with massive PE and concluded that reduced left atrial and pulmonary vein diameters were important findings on MDCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In risk classification, detection of proximal extension in pulmonary embolism patients is a prognostic factor with unrecognized value. 5 The cardiac biomarkers troponin and natriuretic peptide have emerged as promising tools for evaluating the risk among patients diagnosed with APE.…”
Section: Discussionmentioning
confidence: 99%
“…In a quest to evolve CT's competence beyond a pure as-is state interpretation into a tool for prognosis, applying the concept of evaluating the size and function of the right ventricle (RV) for risk assessment has been studied [16][17][18]. Initiated by the study of Reid et al, various studies compared right-ventricular measurements and ratios of right-ventricular diameters to left-ventricular (LV) diameters in a variety of image reconstructions, from true 4-chamber views to axial images [19][20][21][22][23]. Besides one-dimensional measurements, volumetric assessment of the right ventricle, although more timeconsuming, has been shown to be superior in the identification of high-risk patients [24].…”
mentioning
confidence: 99%